2012
DOI: 10.1002/andp.201200099
|View full text |Cite
|
Sign up to set email alerts
|

Application of femtosecond‐pulsed lasers for direct optical manipulation of biological functions

Abstract: Absorption of photon energy by cells or tissue can evoke photothermal, photomechanical, and photochemical effects, depending on the density of the deposited energy. Photochemical effects require a low energy density and can be used for reversible modulation of biological functions. Ultrashort-pulsed lasers have a high intensity due to the short pulse duration, despite its low average energy. Through nonlinear absorption, these lasers can deliver very high peak energy into the submicrometer focus area without c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 75 publications
1
14
0
Order By: Relevance
“…Temperature of all samples increased rapidly at the first 5 min then gradually in accordance with the results in vitro (Fig. 8B) reported that even below the plasma formation threshold energy, laser pulses can also induce irreversible damage to the biological sample by reduction of enzyme activity, protein denaturation and increase in cell membrane stress 38 . In this case, CG-PEG-ICG nanoparticles with ICG concentration of 100, 200 and 500 μg·mL -1 induced irreversible tissue damage which was confirmed in Fig.…”
Section: Photothermal Treatments In Vivosupporting
confidence: 89%
“…Temperature of all samples increased rapidly at the first 5 min then gradually in accordance with the results in vitro (Fig. 8B) reported that even below the plasma formation threshold energy, laser pulses can also induce irreversible damage to the biological sample by reduction of enzyme activity, protein denaturation and increase in cell membrane stress 38 . In this case, CG-PEG-ICG nanoparticles with ICG concentration of 100, 200 and 500 μg·mL -1 induced irreversible tissue damage which was confirmed in Fig.…”
Section: Photothermal Treatments In Vivosupporting
confidence: 89%
“…Our group has recently been engaged in the development of new optical methods that can be used for reversible modulation of biological functions by utilizing femtosecond-pulsed lasers. We have demonstrated that laser-induced photobiomodulation can be mediated by laser-induced intracellular ROS 1 3 . We reported previously that femtosecond laser stimulation induces two distinctive responses in primary cultured smooth muscle cells, i.e., reversible and irreversible responses, depending on the energy delivered 3 .…”
mentioning
confidence: 93%
“…Focused irradiation of high-intensity femtosecond laser can induce non-linear optical effects, such as multiphoton absorption and frequency doubling. As these non-linear phenomena can only occur in the tightly focused area, this reduces out-of-focus signals and has been applied in the field of biomedical imaging as multiphoton microscopy 1 . Recently, it has been reported that femtosecond laser pulses can be used to regulate biological functions, such as muscle contraction 2 3 , blood-brain barrier permeabilization 4 , cellular activation 5 6 , and gene transfection 7 , which is known as reversible biophotomodulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In areas that are closer to everyday life or direct applications, femtosecond lasers have shown their beneficial properties in material processing [50]. In addition, medical utilization is manifold as well, people just have to think about the therapeutic [51], surgical [52] or imaging methods they are used for [53].…”
Section: Applications Of Ultrashort and Few-cycle Wave Formsmentioning
confidence: 99%